Toyin Falola and Akintunde Akinyemi (Eds). Encyclopedia of the Yoruba. Bloomington and Indianapolis: Indiana University Press, 2016. 371pp. - Ibrahim A. Odugbemi (Yoruba Studies Review)
Encyclopedia of the Yoruba is a single-volume encyclopedia that is comprised of 285 entries of short essays written by 188 authors who are predominantly scholars and academic researchers from Africa, Europe and North America. The different word-ranges of the essays vary from 1000 words (for 78 entries) to 750 words (for 88 entries) and 500 words (for 119 entries). Across these entries, the encyclopedia gives a complex, yet detailed, presentation of the Yorùbá, a dominant ethnic group in West Africa and the most prominent African cultural population, identity and presence in the African diaspora including North America, the Caribbean and South America. It presents the Yorùbá with respect to their involvements in, and interactions with, different sociocultural experiences, practices and expressions by “emphasizing the peculiarities, features, and commonalities of the people” (xi). Following an alphabetical ordering, each entry in the encyclopedia is complete on its own as it examines and discusses a subject, subject matter, concept or topic that shares an affiliation with the Yorùbá world in time (the traditional past in all its distant and intricate temporal dimensions and the modern present in all its complex interrelations) and/or space (Yoruba homes across West Africa and the African diaspora. Such concentrations of the entry include persons/personalities, demographics, worldviews and cosmological values and elements, and several material and non-material aspects of the Yorùbá culture and folklore, and their corresponding affiliates. It is important to add that the completeness of the entries is considerably informed by the suitability of the word-ranges used. It is commendable that 358 Ibrahim A. Odugbemi the editors are able to determine the word-range that fits the discourse of every entry and the authors are also able to conform. By writing across the various word-limits, the authors have been able to give adequate information about their subjects of discussion. Each word-limit is moderate enough to convey the basic information on the subject or topic of every entry.